$(\sqrt[13]{7{x}^{2}y}{)}^{3}$

Flambergru
2022-08-04
Answered

Rewrite with rational exponents.

$(\sqrt[13]{7{x}^{2}y}{)}^{3}$

$(\sqrt[13]{7{x}^{2}y}{)}^{3}$

You can still ask an expert for help

Nicole Soto

Answered 2022-08-05
Author has **10** answers

$(\sqrt[13]{7{x}^{2}y}{)}^{3}=[(7{x}^{2}y{)}^{1/13}{]}^{3}$ [As$\sqrt[y]{x}={x}^{1/y}$]

$=(7{x}^{2}y{)}^{(1/13)\ast 3}$ [As $({A}^{x}{)}^{y}={A}^{x\ast y}$]

$=(7{x}^{2}y{)}^{3/13}$

$=(7{)}^{3/13}\ast ({x}^{2}{)}^{3/13}\ast (y{)}^{3/13}$

$=(7{)}^{3/13}\ast (x{)}^{2\ast 3/13}\ast (y{)}^{3/13}$

$=(7{)}^{3/13}\ast (x{)}^{6/13}\ast (y{)}^{3/13}$

Answer:- $(7{)}^{3/13}\ast (x{)}^{6/13}\ast (y{)}^{3/13}$

$=(7{x}^{2}y{)}^{(1/13)\ast 3}$ [As $({A}^{x}{)}^{y}={A}^{x\ast y}$]

$=(7{x}^{2}y{)}^{3/13}$

$=(7{)}^{3/13}\ast ({x}^{2}{)}^{3/13}\ast (y{)}^{3/13}$

$=(7{)}^{3/13}\ast (x{)}^{2\ast 3/13}\ast (y{)}^{3/13}$

$=(7{)}^{3/13}\ast (x{)}^{6/13}\ast (y{)}^{3/13}$

Answer:- $(7{)}^{3/13}\ast (x{)}^{6/13}\ast (y{)}^{3/13}$

Jaylyn Gibson

Answered 2022-08-06
Author has **3** answers

$(\sqrt[13]{\sqrt{7{x}^{2}y}}{)}^{3}\ufeff=(7{x}^{2}y{)}^{3/13}=7{x}^{6/13}{y}^{3/13}$

asked 2020-11-23

To multiply:

The given expression. Then simplify if possible. Assume that all variables represent positive real numbers.

Given:

An expression:$\sqrt{3}(\sqrt{27}-\sqrt{3})$

The given expression. Then simplify if possible. Assume that all variables represent positive real numbers.

Given:

An expression:

asked 2022-07-27

Divide $(x-1{)}^{6}$ by (x+1)

asked 2021-01-28

For the following exercises, use the compound interest formula, $A\left(t\right)=P{(1+\frac{r}{n})}^{nt}$ .

Use properties of rational exponents to solve the compound interest formula for the interest rate, r.

Use properties of rational exponents to solve the compound interest formula for the interest rate, r.

asked 2021-01-22

Use rational exponents to write a single radical expression.

$\sqrt[7]{11}\times \sqrt[6]{13}$

asked 2021-01-31

Find the exact value of each of the remaining trigonometric function of

asked 2021-01-05

The simplified form of the expression

$\sqrt[4]{c{d}^{2}}\times \sqrt[3]{{c}^{2}d}.$

asked 2020-12-16

To calculate: The simplified form of the expression $\frac{\sqrt{12}}{\sqrt{x+1}}.$